Inflorescence morphology and development of suweg (Amorphophallus paeoniifolius (Dennst.) Nicolson - TRI HANDAYANI; YUZAMMI; JULISASI TRI HADIAH (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Hanfayani T, Yuzammi, Hadiah JT. 2020. Inflorescence morphology and development of suweg (Amorphophallus paeoniifolius (Dennst.) Nicolson. Biodiversitas 21: 5835-5844. Inflorescence of Amorphophallus paeoniifolius (Dennst.) Nicolson consists of two main parts: spathe and spadix. Detailed information on its development, however, is not yet available. This study aimed to investigate the development and morphology of suweg’s inflorescence, to reveal the anthesis of male and female flowers, and to observe its insect visitors. The study observed 46 inflorescences, ten of which were measured for detailed developments. Inflorescences were observed from bud emergence to withering during one flowering cycle. The results showed that the flowering process included six phases which altogether required 22 to 36 days, namely the developments of inflorescence bud, cataphyll, spathe and spadix, appendix, fully bloomed inflorescence, and flowers anthesis. The inflorescence height including peduncle was 48–75 cm, spathe 19–50 cm long, spathe circle 65–176 cm, appendix 13–33 cm long, and appendix circle 45–80 cm. Three appendix forms were observed: ovate (43.48%), triangular conic (41.30%), and rounded (15.22%). Female flower anthesis occurred one day prior to male flower anthesis. Insect visitors found during anthesis were Lucilia sericata (Calliphoridae), Sarcophaga sp. (Sarcophagidae), and Trigona speciosa (Apidae).